Analisis Tingkat Kepuasan Pengguna Terhadap Performa Bangunan Gedung di Lingkungan Politeknik Negeri Padang - Hamid, Desmon; Aktorina, Wahyu; Aguskamar, Aguskamar; Atmaja, Jajang; Fitria, Winda (Jurnal Ilmiah Rekayasa Sipil, 2024)
The building performance is an innovative approach that discusses planning, design, construction methods, and the users of the building. To ensure the building functions as intended, maintenance and care are essential. An analysis of user satisfaction regarding building performance reflects users' needs and expectations. Politeknik Negeri Padang, a vocational higher education institution established for 37 years, warrants a user satisfaction analysis of its facilities to maintain comfort in its activities. This research was conducted through a questionnaire survey with 700 respondents, including staff, educators, and students. The analysis using the Suitability Level approach identified three priority indicators for improving building performance: information technology facilities, the condition of public facilities like restrooms, parking, and pantries, and the cleanliness of public toilets. Meanwhile, the Importance and Performance Analysis (IPA) highlighted four key areas for performance enhancement: availability of trash bins and cleanliness of the environment, public facilities such as pantries, toilets, and parking areas, room temperature issues, and information technology facilities like internet connectivity.